The MURDER Strategy Based on Gamification to Enhance StudentsÔÇÖ Interest in Islamic Education and Character Building - Magfirah, Magfirah; Fakhrunnisaa, Nur; Efendi, Erwatul (Journal of Islamic Education Students (JIES), 2025)
Low student interest in Islamic Religious Education and Character Building at the vocational high school (SMK) level remains a challenge, especially under conventional, teacher-centered approaches. This study aimed to enhance studentsÔÇÖ learning interest by applying the gamified MURDER strategy in the classroom. Using the Kurt Lewin Classroom Action Research model, the research was conducted in two cycles comprising planning, action, observation, and reflection stages. Data were collected through observation, questionnaires, interviews, tests, and documentation. Findings showed a significant increase in student learning interest, with student activity rising from 65.5% (pre-cycle) to 95.5% (cycle II), and teacher activity from 81.1% to 95.5%. Students responded positively, describing the learning as more engaging, interactive, and confidence-building. The gamified MURDER strategy proved to be an effective alternative for improving both student interest and instructional quality in Islamic Religious Education and Character Building, and it is recommended for broader use in character-focused, student-centered learning contexts.┬á┬á